Pengaruh Interaksi Edukatif Dan Kemampuan Kognitif Terhadap Minat Belajar Akuntansi Harga Pokok Produk Pada Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2014 - Dewi, Yuni Puspita, Drs. Muhammad Yahya, M.Si (2016)
This research was conducted at the University of Muhammadiyah Surakarta, with the aim of knowing the effect of educational interaction and cognitive ability to learn accounting interest cost of the product at Student Accounting Education Muhammadiyah University of Surakarta Force, 2014. This research uses descriptive quantitative method, because the data used looked realities / symptoms / phenomena that can be classified, relatively fixed, concrete, observable, measurable, and the relationship is causal symptoms are generally carried out in a population or sample. The population of this study were all students of education Accounting Force Surakarta Muhammadiyah University in 2014, amounting to 217 students. The sampling technique used Propsional Sampling as many as 135 respondents. Necessary data obtained through a questionnaire. The questionnaire has previously been tested and tested for validity and reliability were tested. Data analysis technique used is Test Prerequisites Analysis using Normality Test, Test linearity, whereas Hypothesis Testing using Regression Analysis, Test Partial (t test), Test In Unison (Test F), test the coefficient of determination (Adjusted R Square) and Contribution Relative and Effective contribution. The results of the study can be obtained is educative interaction gives the relative contribution of 48.3% and the effective contribution of 35.0%. Educational interactions significantly influence the interest in learning accounting product cost accounting education courses Surakarta Muhammadiyah University class of 2014. It is evident from the t test obtained t for educative interaction variable of 5.705 while ttable 1,978. Cognitive ability gives the relative contribution of 51.7% and the effective contribution of 37.6%. Cognitive Ability significant effect on the interest to study accounting product cost accounting education courses Surakarta Muhammadiyah University class of 2014. This is evidenced by the results obtained t t test for cognitive ability variable of 6.082 while ttable 1,978. Interaction of Educational and Cognitive Ability jointly significant effect on the interest in learning accounting product cost accounting education courses Surakarta Muhammadiyah University class of 2014. This is evident from the test results obtained Fhitung F = 174.872> Ftabel = 3.065. The calculation result shows that the effective contribution of the educative interaction contribution amounting to 35.0% Interest in Learning (X1), while the Cognitive Ability contributed 37.6% (X2), so that the total contribution of the effective interaction of Educational and Cognitive Ability in raising interest rates accounting Learning product cost accounting education courses Muhammadiyah University of Surakarta force in 2014 amounted to 72.6% (R2).